2011
DOI: 10.23907/2011.052
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Death in 14 Month Old Due to Fibromuscular Dysplasia of Atrioventricular Nodal Artery

Abstract: Fibromuscular dysplasia is a non-atherosclerotic, non-inflammatory vascular disease that is most commonly found in the renal arteries of pre-menopausal women. However, this disease entity has rarely been described in the coronary arteries and small cardiac conduction arteries. To our knowledge, there is no recorded case of fibromuscular dysplasia in small cardiac conduction arteries in infants/children. In this report, we present a case of unexplained death of a 14 month old wherein routine histologic examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It is typified by nonatherosclerotic luminal narrowing of this small artery by intimal and medial thickening (Image 54). Several studies have concluded that severe (>75%) narrowing of the AV nodal artery is significant enough to explain sudden cardiac death, with a proposed mechanism of AV nodal ischemia (32, 33).…”
Section: Discussionmentioning
confidence: 99%
“…It is typified by nonatherosclerotic luminal narrowing of this small artery by intimal and medial thickening (Image 54). Several studies have concluded that severe (>75%) narrowing of the AV nodal artery is significant enough to explain sudden cardiac death, with a proposed mechanism of AV nodal ischemia (32, 33).…”
Section: Discussionmentioning
confidence: 99%
“…Burke and Virmani 28 have emphasized that most sudden deaths attributed to FMD of the AV node artery occur during exercise. The youngest reported case of death from FMD of the atrioventricular node artery occurred in a 14-month-old patient 30 . Zack et al 31 have called into question the significance of this lesion, but they do not consider the degree of narrowing of the artery.…”
Section: Intrinsic Vs Extrinsic Causesmentioning
confidence: 99%
“…The youngest reported case of death from FMD of the atrioventricular node artery occurred in a 14-month-old patient. 30 Zack et al 31 have called into question the significance of this lesion, but they do not consider the degree of narrowing of the artery.…”
Section: Intrinsic Vs Extrinsic Causesmentioning
confidence: 99%